UPAYA PEMERINTAH DESA HENDROSARI DALAM MEMPERTAHANKAN DESA WISATA LONTAR SEWU DI ERA PANDEMI COVID-19 - Tri Prasetijowati; Ismail; Dinita Sari (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2022)
This study aims to analyze the formation of the Lontar Sewu Tourism Village before the Covid-19 Pandemic, the efforts of the Hendrosari Village Government in maintaining the Lontar Sewu Tourism Village in the Covid-19 Pandemic era and the factors that influenced the efforts of the Hendrosari Village Government in maintaining the Lontar Sewu Tourism Village. The research method used is descriptive qualitative. The informants in this study were the Head of Hendrosari Village, the Director of the Lontar Sewu BUMDes who doubled as Chair of the Tourism Awareness Group and sellers of food and drinks at tourist attractions. Data collection techniques through observation, interviews and documentation. The data analysis technique used is data collection, data condensation, data presentation, and drawing conclusions. The results showed that: (1) The establishment of the Lontar Sewu Tourism Village was to improve the welfare of the people of Hendrosari Village. The accessibility conditions of Lontar Sewu Tourism Village are good, it has interesting objects, the village government and the community support the tourism village, village security is guaranteed, accommodation in terms of restaurants is available but does not yet have a homestay, the climate is quite cool and it is not related to other tourist objects. (2) The efforts of the Hendrosari Village Government in maintaining a tourist village are digital promotional innovations via Instagram @explore_lontarsewu, adaptation of the implementation of the CHSE health protocol (Cleanliness, Health, Safety, Environment Sustainability) and collaborating with seven stakeholders. (3) Factors that influence it are economic factors (budget funds), social factors (community participation) and environmental factors (conservation of natural potential).